Autoimmune Cytopenias Post Hematopoietic Stem Cell Transplantation in Pediatric Patients With Osteopetrosis and Other Nonmalignant Diseases - Even-Or, Ehud; Schejter, Yael Dinur; NaserEddin, Adeeb; Zaidman, Irina; Shadur, Bella; Stepensky, Polina (Frontiers in Immunology, 2022)
Autoimmune cytopenia (AIC) is a rare complication post hematopoietic stem cell transplantation (HSCT), with a higher incidence in nonmalignant diseases. The etiology of post-HSCT AIC is poorly understood, and in many cases, the cytopenia is prolonged and refractory to treatment. Diagnosis of post-HSCT AIC may be challenging, and there is no consensus for a standard of care. In this retrospective study, we summarize our experience over the past five years with post-HSCT AIC in pediatric patients with osteopetrosis and other nonmalignant diseases. All pediatric patients who underwent HSCT for nonmalignant diseases at Hadassah Medical Center over the past five years were screened for post-HSCT AIC, and data were collected from the patient's medical records. From January 2017 through December 2021, 140 pediatric patients underwent HSCT for osteopetrosis (n=40), and a variety of other nonmalignant diseases. Thirteen patients (9.3%) presented with post-HSCT AIC. Of these, 7 had osteopetrosis (17.5%), and 6 had other underlying nonmalignant diseases. Factors associated with developing AIC included unrelated or non-sibling family donors (n=10), mixed chimerism (n=6), and chronic GvHD (n=5). Treatment modalities included steroids, IVIG, rituximab, bortezomib, daratumumab, eltrombopag, plasmapheresis, and repeated HSCT. Response to treatment was variable; Seven patients (54%) recovered completely, and three patients (23%) recovered partially, still suffering from mild-moderate thrombocytopenia. Three patients died (23%), two following progressive lung disease and one from sepsis and multi-organ failure after a 3rd HSCT. In our experience, post-HSCT AICs in pediatric patients with nonmalignant diseases may pose a challenging post-transplant complication with a variable presentation and a wide spectrum of severity. A relatively high prevalence is seen in patients with osteopetrosis, possibly due to difficult engraftment and high rates of mixed chimerism. There is a dire need for novel treatment modalities for better management of the more severe and refractory cases.